Programmes of frivolity on ice? Hockey, business, diasporic identity and apartheid in South Africa, 1936-1992 (Historia, 2021)
South Africa has a surprisingly long history of the sport perhaps most usually associated with the northern hemisphere: ice hockey. Ice skating was first introduced in the country in the last decade of the nineteenth century as a commercial venture. Entrepreneurs built ice rinks for profit-making purposes and brought showmen from overseas to demonstrate the sport. An ancillary activity was the establishment of ice hockey clubs in 1936 and beyond. Given the strong profit motive, personal and tactical differences between the chief investors and sports administrators inevitably left its imprint on the sport. The extensive involvement of German, Canadian and Swiss immigrants throughout the twentieth century also co-determined the eventual character of the sport. From its inception through to 1991, ice hockey practised racial segregation, operated within apartheid laws and remained an exclusively white activity. Unsurprisingly, the apartheid ice rink also became embroiled in global politics, became a target of the worldwide anti-apartheid sports boycott and was excluded from all international competition from the late 1960s until 1991. This article reclaims some of ice hockey's neglected history in South Africa and investigates the interplay of sport, ice rink entrepreneurship, imperial and foreign identity, and apartheid politics during the twentieth century.